Pengaruh variabel keuangan & non-keuangan terhadap financial distress - Budianto, Budianto; Setiawan, Doddy (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
This study aims to provide empirical evidence of the ability to predict financial distress using financial variables (current ratio, cash flow operation, leverage, gross profit margin, and return on assets) and non-financial variables (going concern opinion, audit report lag, opinion shopping, the additional state capital, and subsidies). Model testing uses three steps. First, financial ratios (CR, CFO, LEV, GPM, ROA); second, non-financial ratios (GCO, ARL, SHOP, ASC, SUB); and third, all variables at once. This study uses panel data (2011-2020) with a sample size of 50 Indonesian SOEs. Data analysis uses ordinal logistic regression. The first test results show that CR and ROA positively affect financial distress, while LEV and GPM have a negative effect. The second test results show ARL has a negative effect, while SHOP and SUB have a positive effect. Meanwhile, the third test results show LEV, GPM, and ASC have a negative effect, while ROA and SUB have a positive effect. Based on the r-squared and correctly predicted values, the third model test results are better than the first and second models. Statistically, the ability to predict financial distress that combines financial and non-financial ratios is better than models that only use financial and non-financial ratios. Financial ratios are the most consistent predictor of financial distress in terms of significance.